The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/lol2.10202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chloride and nutrients on freshwater plankton communities

Abstract: Scientific Significance StatementCurrent water quality guidelines for chloride may not protect aquatic life against rising lake salinity in cold regions where de-icing salts are applied to paved surfaces. Although chloride tolerance of Daphnia pulex  Daphnia pulicaria can increase with food availability, it is unclear how nutrient-and salt-driven changes in phytoplankton and protist composition will impact zooplankton sensitivity to chloride. We exposed freshwater zooplankton communities to a chloride gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The average body mass (biomass/density) of crustaceans decreased with increasing TN, TP, Chl a, and conductivity. Such changes have been widely reported in mesocosm experiments (Thompson and Shurin, 2012;Lind et al, 2018;Moffett et al, 2020;Coldsnow and Relyea, 2021;Greco et al, 2022;Hébert et al, 2022;McClymont et al, 2022) and field investigations (Brucet et al, 2009;He et al, 2020;Zadereev et al, 2022) at moderate to low conductivities. However, at higher conductivities, the food web transforms from threetrophic to two-trophic without fish, and large cladocerans such as Daphnia may become dominant until they reach a critical level at high conductivities (Lin et al, 2017).…”
Section: Zooplankton Decline In Body Mass Along With Eutrophication A...supporting
confidence: 53%
“…The average body mass (biomass/density) of crustaceans decreased with increasing TN, TP, Chl a, and conductivity. Such changes have been widely reported in mesocosm experiments (Thompson and Shurin, 2012;Lind et al, 2018;Moffett et al, 2020;Coldsnow and Relyea, 2021;Greco et al, 2022;Hébert et al, 2022;McClymont et al, 2022) and field investigations (Brucet et al, 2009;He et al, 2020;Zadereev et al, 2022) at moderate to low conductivities. However, at higher conductivities, the food web transforms from threetrophic to two-trophic without fish, and large cladocerans such as Daphnia may become dominant until they reach a critical level at high conductivities (Lin et al, 2017).…”
Section: Zooplankton Decline In Body Mass Along With Eutrophication A...supporting
confidence: 53%
“…Other studies have showed sensitivity at 645 mg Cl − /L (van Meter et al, 2011). Likewise, Greco et al (2021) found cyclopoid copepod abundance declined by 71% at 120 mg Cl − /L. However, Thompson and Shurin (2012) found cyclopoid copepod abundance increased in their 0.3 ppt (about 300 mg Cl − /L) salt treatment.…”
Section: Discussionmentioning
confidence: 96%
“…In our experiment, nauplii and cladocerans were major contributors to the decline caused by elevated salinity. Cladocera have been found to be sensitive to elevated salt concentration (e.g., 5–40 mg Cl − /L in Arnott et al, 2020; Greco et al, 2021). Our result is also consistent with findings from Hintz et al (2017) who reported that nauplii were the most vulnerable zooplankton in their high salinity treatments (≥500 mg Cl − /L).…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater salinization manifests as a distinct water chemistry signature, stemming from road salt applications, faster weathering, and altered soil cation properties in human dominated landscapes (Kaushal et al, 2018). Chloride concentrations (even those below toxicity guidelines for freshwater) effect food web and biotic structur-al components of freshwater ecosystems (Greco et al, 2021;Szklarek et al, 2022). The impacts of chloride on ecosystem processes and function, however, are more nuanced with variable responses being observed across ecosystems with similar levels of chloride exposure.…”
Section: Discussionmentioning
confidence: 99%